The Role of Anesthetic Techniques and Drugs in Laparotomy Cases of Postoperative Ileus - Puspita, Eka Ari; Nugroho, Yudhistiro Andri; Rahmasena, Naomi; Jamil, Ahmad Mochtar; Haniifah, Ulaa; Anas, Muhammad; Rahmah, Laila (Universitas Muhammadiyah Semarang, 2024)
Background: Ileus occurs when there is a non-mechanical decrease or stoppage of the flow of intestinal contents. The cause of ileus has yet to be clearly defined. Various factors influence the risk for an ileus, each affecting a small part of the complex neuroimmune system. The patient will present with bloating and abdominal distension. Plain abdominal films and computed tomography (CT) scans of the abdomen are usually the first diagnostic imaging obtained. The most important principle for treating ileus is treating the underlying cause. Treating the infection, electrolyte abnormalities, and decreasing opiate use can all potentially decrease the durability of an ileus. Anesthesia procedures must be performed to treat patients preoperatively, during surgery, and postoperatively. Enhanced recovery protocols, regional anesthesia, opioid-sparing analgesics, and laparoscopy have all improved the number of postoperative ileus cases.Case Presentation: The following is a 67-year-old male patient who presents with abdominal pain with a scale of 4 out of 10, diagnosed with ileus, which was planned for laparotomy surgery by general anesthesia with supine position.Conclusion:We conclude that anesthetic procedures are critical in ileus patients in performing laparotomy operations, both in selecting anesthetic techniques, anesthetic drugs, and supporting scores (Aldrete score). Before induction, anesthesiologists must carefully assess preoperative and monitor postoperative